Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]5\frac{2}{3}:(-1\frac{2}{15})=\frac{5\times3+2}{3}:(-\frac{1\times15+2}{15})=\frac{15+2}{3}:(-\frac{15+2}{15})\\\\=\frac{17}{3}:(-\frac{17}{15})=\frac{17}{3}\times(-\frac{15}{17})=\frac{1}{3}\times(-\frac{15}{1})=-\frac{15}{3}=-5[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.